Pelatihan Ecobrick Sebagai Upaya Peningkatan Kesadaran Pengelolaan Sampah Plastik pada Anak Sekolah Dasar di Sanggar Literasi Ranggi Deli Serdang - Carlos Marselius Sihombing; Zahra Darmayana; Ega Anysa Gultom; Juli Silalahi; Adinda Farah Diba; Rasenda; Nadia Hani; Zahra Hairani Lubis; Ela Saputri; Devi Ariani; Fauzi Kurniawan; Tegar Anggi Handika (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
The problem of suboptimal plastic waste management and limited literacy facilities are environmental and educational challenges faced by the Ranggi Literacy Studio. This study aims to describe the implementation of ecobrick training as an effort to increase awareness of plastic waste management among children while supporting literacy activities. This study uses a qualitative approach with descriptive methods. The research subjects consisted of 20 children, with 3 informants selected purposively: 2 participants and 1 studio manager. Data collection techniques were carried out through observation, interviews, and documentation, which were analyzed through the stages of data reduction, data presentation, and drawing conclusions. The results show that ecobrick training was implemented through three stages: preparation, implementation, and utilization. This activity was able to increase children's understanding and awareness of plastic waste management and encourage behavioral changes to be more environmentally conscious. In addition, ecobrick products were used as bookshelves that contributed to increasing the tidiness and comfort of literacy activities. Thus, ecobrick training can be an innovative alternative in participatory-based environmental education.